Risk Factors and Short Term Morbidities Associated With Term-Small for Gestational Age Babies Delivered at Nepalgunj Medical College - Kanodia, Piush; Verma, Arun Kumar; Adhikari, Sumit (Journal of Nepalgunj Medical College, 2022)
Introduction: Small for gestational age (SGA) refers to birth weight of neonates less than 10th percentile for gestational age or 2nd standard deviation below the population norms on the growth charts. Aims: To identify common risk factors and common morbidities for small for gestational age babies. Methods: This is a cross sectional descriptive study and it has been conducted at Department of pediatrics, Nepalgunj Medical college which is a tertiary level teaching hospital located in western part of Nepal. All term small for gestational age neonates born during study period from January 2020 to December 2020 were included. Detailed baseline demographic and clinical profile has been collected and recorded in the predesigned Proforma. Results: The most common risk factors associated with small for gestational age babies in our study were maternal hypertension (14.6%) , maternal GDM(9.6%), Urinary Tract Infection (UTI) in 1st or 2nd trimester of pregnancy, maternal anemia, smoking, alcohol consumption, hypothyroidism and congenital heart disease. The most common short term complications associated with Small for gestational age babies were hypoglycemia and Meconium aspiration syndrome. Conclusion: The most common risk factors associated with Small for gestational age babies in our study were maternal hypertension, maternal Gestational diabetes Mellitus (GDM), Urinary Tract Infection in 1st or 2nd trimester of pregnancy, maternal anemia, smoking, alcohol consumption, hypothyroidism and congenital heart disease. The most common short term complications associated with Small for gestational age babies were hypoglycemia and Meconium aspiration syndrome (MAS).